2019
DOI: 10.1016/j.radmeas.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Transforming education with the Timepix detector - Ten years of CERN@school

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It facilitates students to undertake a range of investigative research projects from a varied portfolio of options. For example, these projects have included CERN@School (Whyntie, 2016;Whyntie et al, 2015Whyntie et al, , 2016, where students have been found to have positive experiences, developing research and data analysis skills, and developing wider skills such as collaboration and communication (Hatfield et al, 2019;Parker et al, 2019). Teachers who have facilitated projects for their students report that the experiences produced personal and wider benefits around:…”
Section: Institute For Research In Schools Projectsmentioning
confidence: 99%
“…It facilitates students to undertake a range of investigative research projects from a varied portfolio of options. For example, these projects have included CERN@School (Whyntie, 2016;Whyntie et al, 2015Whyntie et al, , 2016, where students have been found to have positive experiences, developing research and data analysis skills, and developing wider skills such as collaboration and communication (Hatfield et al, 2019;Parker et al, 2019). Teachers who have facilitated projects for their students report that the experiences produced personal and wider benefits around:…”
Section: Institute For Research In Schools Projectsmentioning
confidence: 99%
“…We do not discuss the former here as they are necessarily limited in reach, catering only to heavily bought-in individuals (i.e. typically one to three students; Paull and Xu, 2017) from any given school. Most independent research projects based within schools are not linked to current cutting-edge and novel scientific research topics or questions.…”
Section: Introductionmentioning
confidence: 99%
“…IRIS (Institute for Research in Schools) is a UK charity formally launched in March 2016 (IRIS, 2020), building on the previous CERN@School project conceived in 2007 (Whyntie et al, 2016;Parker et al, 2019). While IRIS' projects cover all the sciences, current physics projects include the aforementioned CERN@School, Higgs Hunters (Barr et al, 2018), LUCID (Furnell et al, 2019;Hatfield et al, 2019), and Webb Cosmic Mining (in preparation for the James Webb Space Telescope).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRIS project CERN@school provides a representative example of the types of engagement and collaborations between school student researchers, teacher-mentors and research scientist partners across the wider group of projects experienced by teachers in this study. CERN@school lends a radiation detector and software to schools which enables the visualisation of alpha, beta and gamma radiation particles (Parker, Thomas, Rushton & Hatfield, 2019). Since 2008, CERN@school has included more than 300 schools, hundreds of teachers and technicians, and involves thousands of students.…”
Section: Introductionmentioning
confidence: 99%